Is the breadth of individualized ranges of optimal anxiety (IZOF) equal for all athletes? A graphical method for establishing IZOF. - Pons, Diana; Balaguer, Isabel; García-merita, M. Luisa (The Spanish Journal of Psychology, 2001)
Sin resumen